(untitled) (Medical Forum Monthly, 2023)
Objective: To determine the frequency of diabetes mellitus in patients with biopsy proven liver cirrhosis. Study Design: A Descriptive, cross-sectional study. Place and Duration of Study: This study was conducted at the Department of Medicine, Bahawal Victoria Hospital, Bahawalpur, from August 2022 to February 2023. Materials and Methods: Patients admitted having biopsy-proven liver cirrhosis were analyzed. Fasting blood glucose and HbA1c levels were evaluated for the presence or absence of diabetes mellitus. Diagnosis of diabetes mellitus was confirmed when there was fasting plasma glucose above 126 mg/dL and HbA1c above 6.5% on two consecutive samples taken at least 12 hours apart. Results: In a total of 240 patients with biopsy proven liver cirrhosis, 138 (57.5%0 were male. The mean age and BMI were 42.87±9.67 years (30 to 70 years) and 27.62±4.25 kg/m2 respectively. Family history of diabetes was present in 102 (42.5%) patients. The frequency of DM was noted in 53 (22.1%) biopsy-proven LC patients. Older age (51-70) was found to have significant association with the presence of DM (34.0% vs. 18.2%, p=0.0138). Increased liver disease severity (higher child pugh class) were noted to have significant association with the presence of DM (p=0.0445). Conclusion: The prevalence of diabetes mellitus was high among patients with biopsy proven liver cirrhosis. Relatively older age, and increased disease severity with linked with significantly higher prevalence of diabetes mellitus in patients with biopsy proven liver cirrhosis.